Association of Lowering Low‐Density Lipoprotein Cholesterol With Contemporary Lipid‐Lowering Therapies and Risk of Diabetes Mellitus: A Systematic Review and Meta‐Analysis. Issue 7 (2nd April 2019) - Khan, Safi U.; Rahman, Hammad; Okunrintemi, Victor; Riaz, Haris; Khan, Muhammad Shahzeb; Sattur, Sudhakar; Kaluski, Edo; Lincoff, A. Michael; Martin, Seth S.; Blaha, Michael J.
Abstract : Background: The relationship between lowering LDL (low‐density lipoprotein) cholesterol with contemporary lipid‐lowering therapies and incident diabetes mellitus (DM) remains uncertain. Methods and Results: Thirty‐three randomized controlled trials (21 of statins, 12 of PCSK9 [proprotein convertase subtilisin/kexin type 9] inhibitors, and 0 of ezetimibe) were selected using Medline, Embase, and the Cochrane Central Register of Controlled Trials (inception through November 15, 2018). A total of 163 688 nondiabetic patients were randomly assigned to more intensive (83 123 patients) or less intensive (80 565 patients) lipid‐lowering therapy. More intensive lipid‐lowering therapy was defined as the more potent pharmacological strategy (PCSK9 inhibitors, higher intensity statins, or statins), whereas less intensive therapy corresponded to active control group or placebo/usual care of the trial. Metaregression and meta‐analyses were conducted using a random‐effects model. No significant association was noted between 1‐mmol/L reduction in LDL cholesterol and incident DM for more intensive lipid‐lowering therapy (risk ratio: 0.95; 95% CI, 0.87–1.04; P =0.30; R 2 =14%) or for statins or PCSK9 inhibitors. More intensive lipid‐lowering therapy was associated with a higher risk of incident DM compared with less intensive therapy (risk ratio: 1.07; 95% CI, 1.03–1.11; P <0.001; I 2 =0%). These results were driven by higher risk of incident DM with statins (risk ratio: 1.10; 95% CI, 1.05–1.15; P <0.001; I 2 =0%), whereas PCSK9 inhibitors were not associated with incident DM (risk ratio: 1.00; 95% CI, 0.93–1.07; P =0.96; I 2 =0%; P =0.02 for interaction). Conclusions: Among intensive lipid‐lowering therapies, there was no independent association between reduction in LDL cholesterol and incident DM. The risk of incident DM was higher with statins, whereas PCSK9 inhibitors had no association with risk of incident DM.